Imagination: a forgotten learning tool box (Praxis Educativa, 2012)
The article presents the research of the Imaginative Education Research Group (IERG) and the current piece of work focuses on children’s imagination and emotions and the ways in which they can influence daily learning in class. This research work shows how these tools can be included in class planning in a simple and innovating way (having the form of stories, by using binary opposites which, in turn, have to be abstract and emotional). The work ends with a brief example of the use of these tools in the planning of a mathematics class about the position value of numbers.
Keywords: imagination; emotion; story; binomial pairs; learning